Inovasi Pengembangan Sistem Absensi Mahasiswa Magang Pada PT PLN ULP Ampera - Farhan Dwi Nugroho; Muhammad Syendi Apriko (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research discusses the development of an attendance system for internship students at PT PLN ULP Ampera which aims to improve the efficiency and accuracy of attendance recording. The current attendance system still uses conventional methods in the form of uploading photos in WhatsApp groups which have several weaknesses such as the possibility of data manipulation and difficulty in verifying attendance. The research method used is Research and Development (R&D) with the stages of needs analysis, system design, prototype development, implementation, and evaluation and maintenance. The research results in the form of a mobilebased attendance application equipped with login features, account registration, dashboard, attendance with photos and GPS, and attendance history. This new system provides a solution for recording attendance that is more accurate, transparent, and integrated, so that it can help manage the internship program more effectively. The development of this system is expected to improve the quality of the internship program and encourage discipline and professionalism of internship students.